Ant Control in the Apiary - William H. Kern, Jr (EDIS, 2017)
Ants are one of a beekeeper’s most common pests, both in the apiary and in the honey house.  Florida and the Southeastern U.S. have a large and diverse ant fauna, with both native and exotic species.  The vast majority of ant species have no impact on our bees or us.  The few pest species can cause serious problems.  We can divide the ants into two pest groups, with the understanding that some can cause both problems at times.